Adaptive Security Orchestration: Intelligent Policy Enforcement - Agarwal, Ashutosh (2025 World Skills Conference on Universal Data Analytics and Sciences (WorldSUAS), 2025)
This paper presents foundational concepts and methodologies for implementing automation in complex security environments, with a focus on the unattended management of network defense systems. It elucidates how the strategic application of automation, driven by continuous operational feedback, creates a robust modeling feedback mechanism for dynamic security policy enforcement. By detailing techniques for streamlining configuration and response, this work offers practical insights into enhancing the efficiency and responsiveness of cybersecurity operations.